SUS para todos: estudo das ações de acolhimento a imigrantes nos hospitais do município de São Paulo - Kawabata, Elena Mitie Miranda [UNIFESP] (2020)
INTRODUCTION: Immigration is a worldwide extension phenomenon which creates an impact at host countries due to the large number of people who find themselves in movement and for the public service conditions in all its segments. The health system of São Paulo city receives an expressive number of immigrants. SUS is an open, worldwide system which hosts all types of people with no distinction. It is guided in humanization and host politics into its hospital and basic assistance network. OBJECTIVES: The main goal of this research is to identify the perception of the professionals regarding to hosting the immigrants to the hospital from the City of São Paulo. METHOD: It is a pool with qualitative approach, the used method in the study was transversal, exploratory and descriptive. Data collection was made through creation of a focal group and, secondly through individual semi structured interviews. The focal group and interviews materials were recorded, transcribed and systematized through the content analysis technique of the thematic type. OUTCOMES AND DISCUSSION: From analysis of the transcriptions, it was verified that the health professionals did not recognize host actions to the immigrants at hospitals, they believe that as a practice to be implemented, host must be based on two premises: ethical values and empathy. It was also observed that there was an absence of protocols which consider some singularities of the immigrant population into hospital assistance. Most of the professionals who answered the pool have technical competences at the health area, are women and have been working for more than ten years in the health segment. FINAL CONSIDERATIONS: Participants could testify the shortage of protocols regarding to care on the immigrant population at hospitals and they also believe that the implementation of flows and protocols might ensure the stability of host actions and their technical procedures and besides that it can also establish standards to the staff and determine the professional competences by including immigrants into the health system effectively. This procedure will make the sizing easier of the interventions as long as the patient is in hospital.